Inventory management practices: A key success towards supply chain performance among industries in Malaysia - Ahmad Mahyadin @ Mahidin, Fariza; Yusoff, Rushami Zien; Saad, Rohaizah (2014)
Today, logistics networks and supply chain are seen as a matter of survival and competitive advantage.Effective supply chain management has become a potential way nowadays to improve performance through matching supply chain practices and competitive advantages in the competitive world.There are many researches were conducted on the area of supply chain practices and its implication towards supply chain performance.However the researched finding seems contradicting.These contradicting finding may results from different reasons such as the level of management commitment, the costs incurred and also due to its level of workers skills.Inventory management across the supply chain is a big challenge for improving coordination among value chain. Controlling inventory is need of the hour as it formulates the business success/failure as competition is intense, growing day-by day. This research conceptualizes and develops the role of inventory management strategies and inventory management practices in fostering supply chain performance. The relationships among different factors are going to be tested in proposed framework using Structural Equation Modeling (SEM) to improve the performance of the supply chain. The insight from this proposed framework will help supply chain managers in implementing inventory management strategies and practices to enhance the overall performance of supply chain.